2009
DOI: 10.1007/s12529-008-9008-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Threat, Risk Perception, and Efficacy Beliefs Related to SARS and Other (Emerging) Infectious Diseases: Results of an International Survey

Abstract: Purpose To study the levels of perceived threat, perceived severity, perceived vulnerability, response efficacy, and selfefficacy for severe acute respiratory syndrome (SARS) and eight other diseases in five European and three Asian countries.Method A computer-assisted phone survey was conducted among 3,436 respondents. The questionnaire focused on perceived threat, vulnerability, severity, response efficacy, and self-efficacy related to SARS and eight other diseases. Results Perceived threat of SARS in case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
259
3
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(300 citation statements)
references
References 31 publications
22
259
3
6
Order By: Relevance
“…In case of an infectious disease pandemic, the willingness and ability of the general public to adhere to recommendations regarding personal hygiene, vaccination, prophylaxis, quarantine, travel restrictions, or closing down of public buildings such as schools (WHO 2006;de Zwart et al 2009) are crucially important. Our findings indicated that there were sufficient preventive behaviors among study participants.…”
Section: Discussionmentioning
confidence: 99%
“…In case of an infectious disease pandemic, the willingness and ability of the general public to adhere to recommendations regarding personal hygiene, vaccination, prophylaxis, quarantine, travel restrictions, or closing down of public buildings such as schools (WHO 2006;de Zwart et al 2009) are crucially important. Our findings indicated that there were sufficient preventive behaviors among study participants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the risk perceptions for emerging infectious diseasesare high, especially when people witness disease outbreaks (8)(9)(10). During the early phases of the outbreak in Iran, CCHF was associated with a relatively high case fatality ratio (up to 20%) (11), hence it was recognized as a deadly disease.…”
Section: Discussionmentioning
confidence: 99%
“…These questions were based on evidence showing that perception of different diseases, and diseases during pandemic phases can be important for the acceptability of different health interventions [42, 43]. With respect to the latter, participants were asked to imagine themselves in the midst of the 2009 H1N1 pandemic and were shown a video clip of press coverage from the time to remind them of the outbreak.…”
Section: Methodsmentioning
confidence: 99%